Parenchymal Blood Volume Assessed by C-Arm-Based Computed Tomography in Immediate Posttreatment Evaluation of Drug-Eluting Bead Transarterial Chemoembolization in Hepatocellular Carcinoma - Syha, Roland; Grözinger, Gerd; Grosse, Ulrich; Maurer, Michael; Zender, Lars; Horger, Marius; Nikolaou, Konstantin; Ketelsen, Dominik (Investigative radiology, 2016)
The aim of this study was to assess clinical utility of the quantitative perfusion parameter called parenchymal blood volume (PBV), as derived from C-arm-based computed tomography (CT), for immediate posttreatment assessment of drug-eluting bead (DEB) transarterial chemoembolization (TACE) in hepatocellular carcinoma (HCC). Twenty-four patients with early- or intermediate-stage HCC received DEB-TACE. A total of 52 HCC lesions were treated and assessed by C-arm CT before and after intervention. C-arm CT consisted of nonenhanced and contrast-enhanced acquisitions; from these, PBV maps were reconstructed. Lesion diameter, maximum PBV, and unenhanced parenchyma density were assessed before and after treatment. Diameter of visible contrast media deposits as well as residual vascularization was assessed after delivery of DEB. All patients underwent follow-up using cross-sectional imaging. All assessed lesions were evaluated concerning modified Response Evaluation Criteria in Solid Tumors for HCC. All treated lesions showed significant decrease in PBV after DEB-TACE (mean difference, -15.61 mL/100 mL, P < 0.0001). Eleven lesions showed residual tumoral perfusion in PBV maps associated with an unfavorable outcome compared with completely treated lesions in terms of a lower tumor shrinkage over time (-0.02 ± 0.49 vs -0.76 ± 0.38; P < 0.0001). A contrast media deposit was seen in 78% of treated HCC lesions with a tendency toward better visibility in encapsulated lesions. Nonenhanced parenchyma density was significantly higher in all treated segments (149.69 ± 58.6 vs 68.42 ± 18.04, P < 0.0001). Parenchymal blood volume values as derived from C-arm CT acquisitions in combination with nonenhanced and contrast-enhanced C-arm CT images are useful in posttreatment assessment of DEB-TACE in HCC. Residual tumor perfusion in PBV maps have predictive potential for mid-term tumor response in HCC and could allow a more individualized treatment schedule for DEB-TACE in HCC patients.